ROLE OF PUBLISHING IN THE CULTURAL AND CREATIVE INDUSTRY - TOMAŠEVIĆ, NIVES; LEBEDA, IVANA LJEVAK (Knygotyra, 2014)
The examination of culture poses a demand for a dialectical reflection on the homology of local and global cultures as a resource to be preserved not only by conservation, but also by future upgrading. Publishing as an industry has a direct impact on both of these segments of culture as a resource or, in other words, through its production, publishing simultaneously conserves the existing cultural values and also upgrades them. Owing to these qualities, publishing has two roles – one pertains to the market in question, whereas the other pertains to culture. These qualities are intertwined within the cultural and creative industry, a sector which is now emerging in Croatia. Another important role within the sector of cultural and creative industry belongs to the book, which is a product of the publishing industry. This research regards the book as a product of the publishing industry for which an attractive niche in the market should be found and takes the position that from the sales perspective, a potential reader, i.e. a future consumer of this cultural good, should be approached in an understandable and efficient manner. This means that the function of the book is also twofold (both a cultural and an economic good). Therefore, the book demands a comprehensive x approach that combines local and global cultures around the fact that it is precisely the book that is the basic means by which language capital of a specific cultural identity, as well as cultural diversity on a global scale, is nurtured. KEYWORDS: publishing, literature, cultural good, cultural and creative industry, culture, art.